Tanggung Jawab Notaris atas Kelalaian Penomoran Ganda pada Akta Otentik - Gina Anjelita (Dinasti Research, 2025)
A notary can commit negligence with the same numbering of two different notary deeds or what is often called double numbering. This is certainly detrimental to the credibility of the authentic deed. This certainly violates the obligations of Notaries as stated in Article 16 and 17 of the UUJN. The purpose of this study is to analyze and describe the responsibility of notaries for negligence in double numbering in authentic deeds and the validity of authentic deeds with double numbering. This research is processed with a normative juridical approach method, namely by looking at law as a set of regulations/rules or doctrines that have a normative nature (law in book). As a result of the problem, the Notary is responsible for his negligence in giving a double deed numbering on the authentic deed he made. Sanctions that can ensnare Notaries are in the form of administrative sanctions, civil sanctions, and/or criminal sanctions. However, even if there is a double numbering on the deed, it does not necessarily invalidate the validity of a deed. As long as the contents of the deed have met the conditions for the validity of an agreement as stipulated in Article 1320 of the Civil Code, the deed still has binding legal force.